Acrylate modified rubber composition as well as preparation method and application thereof
Through the introduction of acrylic and methyl acrylic acrylic hydroglcented on the SBS or SIS rubber molecular chain, and the cross -linking response to form an acrylic altering rubber resin, the existing rubber pressure -sensitive glue -to -polar material adhesion performance and the adeptic materials and The problem of poor impact performance realizes higher adhesion strength, stretching strength and impact resistance.
Patent Information
- Application Number
- CN202411626486.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing SBS or SIS rubber pressure-sensitive adhesives have poor adhesive properties and impact resistance to polar materials, and have poor weather resistance.
By introducing acrylic and methyl acrylic acid on the rubber molecular chain to form a methyl acrylic hydropacxidide glycerin, the rubber is formed, and the increase in the C = C double bond and the epoxy group through the GMA structure, further further A cross -linking response was performed to obtain acrylate modified rubber resin.
Improve the compatibility and decentralization uniformity of rubber in the adhesive system, improve the adhesion strength, stretch strength and impact resistance of the polar base, and enhance the weather resistance of the material.
Smart Images

Figure CN119351009A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an acrylate modified rubber composition, a preparation method and application thereof. Background Art
[0002] Thermoplastic styrene butadiene rubber, also known as polystyrene butadiene copolymer, is a rubber material with high elasticity and excellent processing properties. Its performance is close to or better than that of natural rubber. It is widely used in tires, tapes, hoses, wires and cables, medical devices and other fields. It is an important product of the general synthetic rubber industry and one of the earliest synthetic rubber varieties to achieve industrial production.
[0003] Butadiene-styrene block copolymer (SBS) and styrene-isoprene block copolymer (SIS) are important thermoplastic elastomers. They are triblock copolymers formed by block copolymerization. They have low melt viscosity, are easily compatible with various tackifying resins, have good viscosity and elasticity, and are widely used as pressure-sensitive adhesives. The performance of rubber elastomers is closely related to their macromolecular chain structure. Their excellent elasticity comes from the micro-domains formed by a large number of polybutadiene (PB) or polyisoprene (PI) soft segments in the aggregated state. The separation of polystyrene (PS) and rubber micro-domains gives the product a strong cross-linking structure and cohesion.
[0004] In the copolymer molecular chain structure, the middle segment is a flexible and continuous rubber segment (PB or PI), and the two ends are hard segment plastic phases composed of PS, with a microphase separation structure in which hard segment microregions are dispersed in the soft segment matrix. At room temperature, the aggregation area is hard spherical, constraining the rubber phase and fixing it, which has both physical crosslinking and reinforcement effects on the rubber segment. At higher temperatures, the PS segment softens, the crosslinking is destroyed, and it shows plasticity and fluidity, and re-forms a network structure after cooling.
[0005] The structural units of SBS and SIS are composed of non-polar styrene, butadiene or isoprene. Polar materials usually have a certain charge distribution, which makes them have good adsorption and adhesion properties for polar substances. When SBS and SIS composed of non-polar monomers come into contact with polar materials, the mismatch in charge distribution between the two leads to weak interaction between non-polar and polar materials. This results in the inability of pressure-sensitive adhesives with SBS and SIS as the main components to effectively bond polar materials during application, thus affecting the use effect. In addition, since the chain structure of SBS and SIS contains unsaturated double bonds, they are easily oxidized, resulting in poor weather resistance.
[0006] The main methods for modifying the macromolecular chain of SBS or SIS are graft copolymerization and epoxidation modification. In the presence of a peroxide initiator, other polar polymer chain segments can be introduced into the SBS or SIS molecular chain through graft copolymerization to carry out a mono- or even poly-grafting reaction. Epoxidation modification is another method for modifying the macromolecular chain of SBS or SIS. By using performic acid generated by the reaction of hydrogen peroxide and formic acid as an oxidant, SBS or SIS is epoxidized. These two modification methods can enable SBS or SIS to maintain its thermoplastic elastomer characteristics while obtaining better physical and chemical properties, such as heat resistance and bonding properties, thereby broadening its application areas. Summary of the invention
[0007] One of the purposes of the present invention is to provide an acrylate modified rubber composition to solve the problem in the prior art that SBS or SIS rubber pressure sensitive adhesive has poor bonding performance and impact resistance to polar materials;
[0008] The second object of the present invention is to provide a method for preparing an acrylate modified rubber composition;
[0009] A third object of the present invention is to provide an acrylate modified rubber composition for use as an adhesive in the fields of machinery, electronics, and medicine.
[0010] The purpose of the present invention can be achieved through the following technical solutions:
[0011] In a first aspect, the present invention provides an acrylate modified rubber composition, which is composed of a solute and a solvent, wherein the solute comprises the following components in parts by mass:
[0012]
[0013]
[0014] The total mass fractions of the acrylate modified rubber resin, tackifying resin, aging agent, free radical initiator, crosslinking agent and filler is 100 parts.
[0015] As a further embodiment of the present invention, the acrylate-modified rubber resin is prepared by the following steps:
[0016] S1: Under the protection of N2, add the rubber copolymer into the container, slowly raise the temperature to 160-180°C, add glycidyl methacrylate and dicumyl peroxide, continue heating to 200-210°C at a speed of 120-150 r / min, stir and mix to obtain a glycidyl methacrylate grafted rubber mixture;
[0017] S2: dissolving the glycidyl methacrylate grafted rubber mixture in chloroform and soaking it for 3 hours, placing it in anhydrous ethanol under high-speed stirring conditions for precipitation, filtering and drying to obtain the glycidyl methacrylate grafted rubber;
[0018] S3: Add hydroquinone (inhibitor) and toluene to the glycidyl methacrylate grafted rubber, stir and heat to 85-95°C, drop a mixture of N,N-dimethylaniline (catalyst) and acrylic acid, stir and react for 3-5 hours to obtain acrylate-esterified glycidyl methacrylate grafted rubber, i.e., acrylate-modified rubber resin.
[0019] Furthermore, the rubber copolymer in S1 includes isobutylene-isoprene block copolymer (butyl rubber), butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIS), natural rubber, and butadiene rubber.
[0020] Furthermore, the amount of glycidyl methacrylate in S1 is 4.5-5.5wt% of the rubber copolymer, and the amount of dicumyl peroxide is 0.08-0.12wt% of the rubber copolymer.
[0021] Furthermore, in the S3, the mass ratio of the glycidyl methacrylate grafted rubber, acrylic acid and toluene is 5:1:2.
[0022] Furthermore, in the S3, the amount of N,N-dimethylaniline used is 5wt% of the acrylic acid; the amount of hydroquinone used is 3wt% of the acrylic acid.
[0023] As a further embodiment of the present invention, the tackifying resin is a solid tackifying resin or a mixture of a solid tackifying resin and a liquid tackifying resin.
[0024] The softening temperature of the liquid tackifying resin is 0 to 35°C;
[0025] The solid tackifying resin is one or more of rosin resin, rosin phenol resin, terpene resin, terpene phenol resin, and petroleum resin, and the softening temperature is ≥80°C; preferably, the softening temperature is ≥100°C; the phenolic resin preferably has a softening temperature above 120°C, and the high softening point of the resin can improve the thermal stability of the rubber composition.
[0026] As a further scheme of the present invention, the aging agent is one or a combination of hindered phenols, amines, phosphites, and sulfide antioxidants; preferably, the aging resistance of the rubber composition is improved by a compounding method. Specifically, the aging agent is one or a combination of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, butylmalonic acid ester mixture, tris[2,4-di-tert-butylphenyl] phosphite, 2,2-dimethylenebis-(4-methyl-6-tert-butylphenol).
[0027] As a further embodiment of the present invention, the free radical initiator is any one of dibenzoyl peroxide, cyclohexanone peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, and 1-hydroxycyclohexyl phenyl ketone.
[0028] As a further embodiment of the present invention, the cross-linking agent is any one of hexamethylene isocyanate (HDI), 2,4-toluene diisocyanate (TDI), and isophorone diisocyanate (IPDI).
[0029] As a further embodiment of the present invention, the filler is one or any combination of nano silver wire, silver powder, nickel powder, copper powder, silver-coated copper powder, carbon nanotubes, graphene, fumed silica, alumina, boron nitride, calcium carbonate, and titanium dioxide.
[0030] As a further embodiment of the present invention, the solvent is one or a mixture of toluene, xylene, ethyl acetate, butanone, n-hexane and cyclohexanone.
[0031] In a second aspect, the present invention provides a method for preparing an acrylate modified rubber composition, comprising the following steps:
[0032] The solute is dissolved and dispersed in a solvent at a solid content of 50%, and after being fully mixed and allowed to stand for defoaming, an acrylate modified rubber composition is obtained.
[0033] In a third aspect, the present invention provides an acrylate-modified rubber composition for use as an adhesive in the fields of machinery, electronics, and medical treatment.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention provides an acrylate modified rubber composition, wherein a rubber modified by acrylate and glycidyl methacrylate is selected as the main material of the adhesive, and glycidyl methacrylate is introduced into the side chain structure of the rubber by using the fact that it contains both C=C double bonds and epoxy groups, thereby obtaining a glycidyl methacrylate grafted rubber product; and then a polyacrylate copolymer cross-linked modified rubber is further obtained by using the ring-opening cross-linking reaction of the epoxy group in the GMA structure with hydroxyethyl acrylate, (meth) acrylic acid, and isocyanate. The compatibility and dispersion uniformity of the SBS or SIS after the polyacrylate copolymer cross-linking modification in the adhesive system are improved by the volume expansion effect of the C=C double bonds and epoxy groups in the GMA structure, thereby improving the impact resistance; the introduction of the acrylate segment improves the tensile strength of the material, the bonding strength to the polar substrate, and the weather resistance. The prepared acrylate modified rubber composition has excellent bonding performance to the polar substrate, tensile performance, and impact resistance, and can meet the application requirements in the fields of machinery, electronic medicine, etc. as an adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The present invention will be further described below in conjunction with the accompanying drawings.
[0037] Figure 1 It is the infrared thin film spectra of SBS and SBS-g-GMA of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, in the present invention, parameters such as the heating rate, cooling rate, and heating rate depend on the instruments used and only need to meet industry standards.
[0040] Acrylate modified rubber resin is prepared by the following steps:
[0041] S1: Rubber copolymer, glycidyl methacrylate (GMA) and dicumyl peroxide (DCP) are weighed in a mass ratio of 100:4.5-5.5:0.08-0.12;
[0042] Under the protection of N2, add the rubber copolymer into the container, slowly heat it to 160-180°C, add glycidyl methacrylate and dicumyl peroxide, continue heating to 200-210°C at a speed of 120-150 r / min, stir and mix to obtain a glycidyl methacrylate grafted rubber mixture;
[0043] S2: After the glycidyl methacrylate grafted rubber mixture is dissolved and soaked in chloroform for 3 hours, it is precipitated in anhydrous ethanol under high-speed stirring at a speed of 800 to 1200 r / min, the filtrate is filtered out, and the obtained solid is placed in a vacuum oven to dry to obtain the glycidyl methacrylate grafted rubber;
[0044] S3: Glycidyl methacrylate grafted rubber, acrylic acid, toluene, N,N-dimethylaniline and hydroquinone are weighed in a mass ratio of 5:1:2:0.05:0.03;
[0045] Add hydroquinone and toluene to the glycidyl methacrylate grafted rubber, stir and heat to 85-95°C, add dropwise a mixture of N,N-dimethylaniline and acrylic acid, stir and react for 3-5 hours to obtain acrylate-esterified glycidyl methacrylate grafted rubber, i.e., acrylate-modified rubber resin.
[0046] In a specific implementation case, the rubber copolymer includes isobutylene-isoprene block copolymer (butyl rubber), butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIS), natural rubber, and butadiene rubber.
[0047] An acrylate modified rubber composition, composed of a solute and a solvent with a solid content of 50%, wherein the solute comprises the following components by mass:
[0048]
[0049] The sum of the mass parts of the acrylate modified rubber resin, tackifying resin, aging agent, free radical initiator, crosslinking agent and filler is 100 parts;
[0050] The method for preparing the acrylate modified rubber composition comprises the following steps:
[0051] The above materials are used as solutes, dissolved and dispersed in a solvent at a solid content of 50%, fully mixed by a three-roll mill, and allowed to stand for defoaming to obtain an acrylate modified rubber composition.
[0052] In a specific implementation case, the tackifying resin is a solid tackifying resin or a mixture of a solid tackifying resin and a liquid tackifying resin.
[0053] The softening temperature of the liquid tackifying resin is 0 to 35°C;
[0054] The solid tackifying resin is one or more of rosin resin, rosin phenol resin, terpene resin, terpene phenol resin, and petroleum resin, and the softening temperature is ≥80°C; preferably, the softening temperature is ≥100°C; the phenolic resin preferably has a softening temperature above 120°C, and the high softening point of the resin can improve the thermal stability of the rubber composition.
[0055] In a specific implementation case, the aging agent is one or a combination of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, a mixture of butyl malonates, tris[2,4-di-tert-butylphenyl] phosphite, and 2,2-dimethylenebis-(4-methyl-6-tert-butylphenol).
[0056] In a specific implementation case, the free radical initiator is any one of dibenzoyl peroxide, cyclohexanone peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, and 1-hydroxycyclohexyl phenyl ketone.
[0057] In a specific implementation case, the cross-linking agent is any one of hexamethylene isocyanate, 2,4-toluene diisocyanate, and isophorone diisocyanate.
[0058] In a specific implementation case, the filler is one or any combination of nano silver wire, silver powder, nickel powder, copper powder, silver-coated copper powder, carbon nanotubes, graphene, fumed silica, aluminum oxide, boron nitride, calcium carbonate, and titanium dioxide.
[0059] In a specific implementation case, the solvent is one or a mixture of toluene, xylene, ethyl acetate, butanone, n-hexane, and cyclohexanone.
[0060] An application method of an acrylate modified rubber composition comprises the following steps:
[0061] The acrylate modified rubber composition is coated on the release film using a manual scraper to form a glue liquid with a certain thickness, and is baked in temperature zones of 30-35°C, 40-45°C, 60-75°C, 90-100°C, and 110-120°C in sequence to obtain a pressure-sensitive adhesive film with a certain thickness for use as an adhesive.
[0062] In the following Preparation Example 1-Preparation Example 2:
[0063] Glycidyl methacrylate (GMA), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.;
[0064] Dicumyl peroxide (DCP), Aldrich, purity 98%.
[0065] In the following Examples 1 to 7 and Comparative Examples 1 to 2:
[0066] The tackifying resin is composed of 6 parts of Cray Valley, Wingtack STS with a softening point of 94°C, 16 parts of Eastman PICCOLYTE S135 terpene resin with a softening point of 135°C, 16 parts of Kraton, Sylvarestr B115 terpene resin with a softening point of 115°C, and 6 parts of Kraton, Sylvatac RE10L liquid rosin ester;
[0067] The aging agent is selected from Irganox 1076, BASF;
[0068] The free radical initiator is dibenzoyl peroxide, selected from Aladdin reagent;
[0069] The cross-linking agent is 2,4-toluene diisocyanate selected from TCI;
[0070] The filler is fumed silica, selected from Wacker HDKH15.
[0071] Preparation Example 1
[0072] This preparation example provides an acrylate modified rubber resin, which is prepared by using a butadiene-styrene block copolymer (SBS) through the following steps:
[0073] S1: Rubber copolymer, glycidyl methacrylate and dicumyl peroxide: 100 g SBS, 5 g glycidyl methacrylate and 0.1 g dicumyl peroxide were weighed in a mass ratio of 100:5:0.1;
[0074] 100g of SBS was added into a round-bottom flask equipped with a mechanical stirrer, a thermometer, a nitrogen inlet tube, and a feeding device, and the temperature was slowly raised to 170°C under N2 protection; 5g of glycidyl methacrylate and 0.1g of diisopropylbenzene peroxide were added thereto, and the mixture was heated to 200°C at a speed of 130r / min, and the mixture was stirred for reaction for 1h to obtain a glycidyl methacrylate-grafted rubber mixture;
[0075] S2: After the glycidyl methacrylate grafted rubber mixture was dissolved and soaked in chloroform for 3 hours, it was precipitated in anhydrous ethanol under high-speed stirring at a speed of 1000 r / min, the filtrate was filtered out, and the obtained solid was placed in a vacuum oven and dried to obtain glycidyl methacrylate grafted rubber (SBS-g-GMA);
[0076] The reaction process was monitored by Fourier thin film (50-10 μm) infrared spectroscopy, using the carbonyl group at 1735 cm -1The absorbance at is used to track the grafting of the product during the reaction, such as Figure 1 The infrared film spectra of SBS rubber and SBS-g-GMA rubber are shown in Figure 1. Figure 1 It can be seen that at 1735cm -1 At , the carbonyl characteristic peak appears, indicating that glycidyl methacrylate is effectively grafted onto SBS, providing a basis for the subsequent esterification of acrylate;
[0077] When the carbonyl absorption peak in the glycidyl methacrylate grafted rubber film sample no longer increases, the maximum grafting rate is calculated to be 0.57wt% using C=M-WW×100%, where C is the grafting rate, M is the mass of the product after precipitation and drying with anhydrous ethanol, in g, and W is the feed amount of SBS, in g.
[0078] The mass grafting degree of the glycidyl methacrylate grafted rubber is 87 wt %, the molar grafting degree is 35 mol %, and the monomer conversion rate of glycidyl methacrylate is 18 wt %.
[0079] S3: Glycidyl methacrylate grafted rubber, acrylic acid, toluene, N,N-dimethylaniline and hydroquinone are weighed in a mass ratio of 5:1:2:0.05:0.03. 50 g of glycidyl methacrylate grafted rubber, 0.3 g of hydroquinone, 20 g of toluene, 0.5 g of N,N-dimethylaniline and 10 g of acrylic acid;
[0080] 50g of glycidyl methacrylate grafted rubber, 0.3g of hydroquinone and 20g of toluene are added to a four-necked flask equipped with a stirrer, a constant pressure dropping funnel, a condenser and a thermometer. Under N2 protection, the temperature is raised to 90°C, and the mixture is stirred and mixed at a speed of 150r / min. A mixed solution consisting of 0.5g of N,N-dimethylaniline and 10g of acrylic acid is added dropwise thereto. The dropping speed is controlled so that the addition is completed within 30min. The mixture is stirred and reacted at 90°C for 4h to obtain acrylate-esterified glycidyl methacrylate grafted rubber resin, i.e., acrylate-modified rubber resin.
[0081] The reaction process was monitored by Fourier thin film (50-10 μm) infrared spectroscopy, tracking the carbonyl at 1710 cm -1 The absorption peak at 1634cm -1 The absorption peak at 1634 cm -1 When the absorption peak no longer increases, the maximum conversion rate is calculated to be 95wt% using C=M-WW×100%, where C is the acrylic acid conversion rate, M is the mass of the dried product in g, and W is the feed amount of acrylic acid in g.
[0082] In this preparation example:
[0083] The styrene-butadiene block copolymer (SBS) is selected from thermoplastic styrene-butadiene rubber, Kraton SBSD1184A from the United States, with 30% styrene block.
[0084] Preparation Example 2
[0085] This preparation example provides an acrylate modified rubber resin, which is different from Preparation Example 1 in that only the butadiene-styrene block copolymer (SBS) is replaced by a styrene-isoprene block copolymer (SIS), and the other steps and parameters remain the same;
[0086] In this preparation example, the styrene-isoprene block copolymer (SIS) is selected from thermoplastic styrene-butadiene rubber, Kraton SISD1163 from the United States, with a styrene block content of 15%.
[0087] Embodiment 1-5
[0088] A method for preparing an acrylate-modified rubber composition, using the acrylate-modified rubber resin prepared in Preparation Example 1, comprises the following steps:
[0089] 100 parts by weight of solute (acrylate modified rubber resin, tackifying resin, aging agent, free radical initiator, crosslinking agent and filler) are dissolved and dispersed in toluene at a solid content of 50%, fully mixed by a three-roll mill, and allowed to stand for defoaming to obtain an acrylate modified rubber composition.
[0090] In Examples 1 to 5, the components and mass fractions of the solutes are shown in Table 1:
[0091] Table 1
[0092]
[0093] Embodiment 6-7
[0094] A method for preparing an acrylate-modified rubber composition, using the acrylate-modified rubber resin prepared in Preparation Example 2, comprises the following steps:
[0095] 100 parts by weight of solute (acrylate modified rubber resin, tackifying resin, aging agent, free radical initiator, crosslinking agent and filler) are dissolved and dispersed in toluene at a solid content of 50%, fully mixed by a three-roll mill, and allowed to stand for defoaming to obtain an acrylate modified rubber composition.
[0096] In Example 6-Example 7, the components and mass fractions of the solutes are shown in Table 2:
[0097] Table 2
[0098]
[0099] Comparative Example 1
[0100] A method for preparing an SBS rubber composition, using a styrene-butadiene block copolymer (SBS), comprises the following steps:
[0101] 100 parts by weight of solute (SBS, tackifying resin, aging agent, free radical initiator, crosslinking agent and filler) were dissolved and dispersed in toluene at a solid content of 50%, fully mixed by a three-roll mill, and allowed to stand for defoaming to obtain an SBS rubber composition.
[0102] In this comparative example, the styrene-butadiene block copolymer (SBS) is an unmodified styrene-butadiene rubber selected from thermoplastic styrene-butadiene rubber, Kraton SBSD1184A from the United States, with a styrene block content of 30%.
[0103] Comparative Example 2
[0104] A method for preparing a SIS rubber composition, using a styrene-isoprene block copolymer (SIS), comprises the following steps:
[0105] 100 parts by weight of solute (SIS, tackifying resin, aging agent, free radical initiator, crosslinking agent and filler) were dissolved and dispersed in toluene at a solid content of 50%, fully mixed by a three-roll mill, and allowed to stand for defoaming to obtain a SIS rubber composition.
[0106] In this comparative example, the styrene-isoprene block copolymer (SIS) is an unmodified styrene-butadiene rubber selected from thermoplastic styrene-butadiene rubber, Kraton SISD1163 from the United States, with a styrene block content of 15%.
[0107] In Comparative Example 1-Comparative Example 2, the components and mass fractions of the solute are shown in Table 3:
[0108] Table 3
[0109]
[0110] Application and performance testing:
[0111] The acrylate modified rubber compositions prepared in Examples 1 to 7 were respectively coated on PET release films using a manual scraper to adjust the thickness to a certain level. The films were then placed in an oven at 35°C, 40°C, 60°C, 90°C, and 115°C for 10 min each to form solidified samples, thereby obtaining pressure-sensitive adhesive films of a certain thickness.
[0112] The SBS rubber composition prepared in Comparative Example 1 and the SIS rubber composition prepared in Comparative Example 2 were respectively coated on a PET release film using a manual scraper to adjust a certain thickness. The thin film samples were then sequentially placed in an oven at 35°C, 40°C, 60°C, 90°C, and 115°C for 10 min each to form a cured sample, thereby obtaining a pressure-sensitive adhesive film with a certain thickness.
[0113] The pressure-sensitive adhesive film samples obtained by the above steps of Example 1 to Example 7 and Comparative Example 1 to Comparative Example 2 were subjected to performance tests such as thickness, peel strength, tensile strength, and elongation at break:
[0114] Peel strength test: The samples were prepared and 180° peel strength test was performed according to standard ASTM D3330. The test substrates were steel plate (SUS304) and matte black ink surface (which was pasted on the steel plate with double-sided tape for testing).
[0115] Tensile fracture test: Cut 3 50mm*15mm strips along the gluing direction and the vertical direction respectively, and reserve 20mm for fixing at both ends. The tensile fracture test part is 10mm*15mm. Install it vertically and clamp it on the fixture. Test at a tensile speed of 200mm / min until the strip breaks.
[0116] DuPont impact test: The film is die-cut into 2mm wide circular samples, and 24.5mm*24.5mm and 20.5mm*20.5mm square PC sheets are attached to both sides respectively. Stainless steel balls of different masses are dropped vertically from a height of 1m to impact the PC sheets. The ball number and weight of the cracked PC sheets are recorded to calculate the impact energy that the film can withstand when the steel balls fall.
[0117] The test results are shown in Table 4:
[0118] Table 4
[0119]
[0120] It can be seen from Table 4 that Comparative Example 1 and Comparative Example 2 use SBS and SIS as the main base resins of the adhesive respectively, and there is no chemical crosslinking in the unmodified state. When the thickness is the same, their performance in all aspects is relatively poor.
[0121] Examples 1 to 7 are 100 μm acrylic modified rubber composition films prepared according to the present invention. Among them, Examples 1 to 5 are modified SBS rubber composition films, and Examples 6 and 7 are modified SIS rubber composition films. At the same time, the median, upper limit and lower limit of the above two main materials are explained. It can be seen from the above table that Examples 1 to 7 all achieve effective cross-linking of modified rubber and acrylate, and the viscosity, tensile strength, elongation at break and impact resistance of the film under different test conditions are maintained at a relatively high level. It can be seen that the acrylate modified rubber composition disclosed in this application can effectively improve the viscosity and impact resistance of thermoplastic butyl rubber. Under normal use conditions, it has excellent bonding strength to metals and polar substrates, and has excellent impact resistance at a very small bonding area. The acrylate modified rubber composition disclosed in the present invention can be used as an adhesive in the fields of machinery, electronics, and medical treatment.
[0122] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0123] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An acrylate modified rubber composition, characterized in that: The composition is composed of solute and solvent with a solid content of 50%, and the solute includes the following components by mass: The sum of the mass parts of the acrylate modified rubber resin, the tackifying resin, the aging agent, the free radical initiator, the crosslinking agent and the filler is 100 parts.
2. An acrylate modified rubber composition according to claim 1, characterized in that: The acrylate modified rubber resin is prepared by the following steps: S1: Under the protection of N2, add the rubber copolymer into the container, raise the temperature to 160-180°C, add glycidyl methacrylate and dicumyl peroxide, continue heating to 200-210°C at a speed of 120-150r / min, stir and mix evenly and react for a certain time to obtain a glycidyl methacrylate grafted rubber mixture; S2: dissolving the glycidyl methacrylate grafted rubber mixture in chloroform and soaking it for 3 hours, placing it in stirred anhydrous ethanol for precipitation, filtering and drying to obtain the glycidyl methacrylate grafted rubber; S3: Add hydroquinone and toluene to the glycidyl methacrylate grafted rubber, stir and heat to 85-95°C, drop a mixed solution of N,N-dimethylaniline and acrylic acid, stir and react for 3-5 hours to obtain an acrylate modified rubber resin.
3. An acrylate modified rubber composition according to claim 2, characterized in that: The rubber copolymers include isobutylene-isoprene block copolymers, butadiene-styrene block copolymers, styrene-isoprene block copolymers, natural rubber, and butadiene rubber.
4. An acrylate modified rubber composition according to claim 2, characterized in that: The amount of glycidyl methacrylate in S1 is 4.5-5.5wt% of the rubber copolymer, and the amount of dicumyl peroxide is 0.08-0.12wt% of the rubber copolymer; And / or, in S3, the mass ratio of glycidyl methacrylate grafted rubber, acrylic acid and toluene is 5:1:2; the amount of N,N-dimethylaniline is 5wt% of the acrylic acid; and the amount of hydroquinone is 3wt% of the acrylic acid.
5. The acrylate modified rubber composition according to claim 1, characterized in that: The tackifying resin is a solid tackifying resin or a mixture of a solid tackifying resin and a liquid tackifying resin.
6. An acrylate modified rubber composition according to claim 5, characterized in that: The softening temperature of the liquid tackifying resin is 0 to 35°C; The solid tackifying resin is one or more of rosin resin, rosin phenol resin, terpene resin, terpene phenol resin and petroleum resin, and the softening temperature is ≥80°C.
7. The acrylate modified rubber composition according to claim 1, characterized in that: The aging agent is one or a combination of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, butylmalonic acid ester mixture, tris[2,4-di-tert-butylphenyl]phosphite, 2,2-dimethylenebis-(4-methyl-6-tert-butylphenol).
8. The acrylate modified rubber composition according to claim 1, characterized in that: The solvent is one or a mixture of toluene, xylene, ethyl acetate, butanone, n-hexane and cyclohexanone.
9. A method for preparing the acrylate modified rubber composition according to claim 1, characterized in that: The following steps are involved: The solute is dissolved and dispersed in a solvent at a solid content of 50%, and after being fully mixed and allowed to stand for defoaming, an acrylate modified rubber composition is obtained.
10. Use of the acrylate modified rubber composition according to claim 1 in an adhesive.